THE IMPACT OF GREEN HUMAN RESOURCE MANAGEMENT ON ENVIRONMENTAL PERFORMANCE AMONG EMPLOYEES OF ENVIRONMENTALLY FRIENDLY COMPANIES IN BATAM - Muchsinati, Evi Silvana; Saidah Dulfi; Antony Sentosa (Program Sarjana Manajemen Universitas Internasional Batam, 2025)
Efforts by companies to achieve long-term sustainability by emphasizing the importance of Environmental Performance (EP) align with the goals of the SDGs, where environmental preservation is crucial for maintaining sustainability. The manufacturing sector has implemented Green Human Resource Management (GHRM) practices to address this issue. This study aims to demonstrate that the GHRM variable affects Environmental Performance through Organizational Citizenship Behavior (OCB) as a mediating variable. The research sample consists of 363 respondents from seven environmentally friendly companies in Batam. Data analysis was conducted using SEM Partial Least Squares (PLS) by distributing questionnaires to the employees of these companies. The results indicate a significant effect of GHRM and OCB on EP, both directly and indirectly, in environmentally friendly companies in Batam.